Televised Campus Dreams: The Emotional Influence of Pakistani Dramas on University Girls' Romantic Expectations - Erum Waheed; Dr.Noman Ahmed Ansari; Madeeha Fasahat; Muhammad Waqas Awan (`, 2025)
In the framework of Pakistani media consumption under the television, the study looks at the cultivation effect in relation to expectations related to romantic relationships among female students at Sindh Jamshoro University in Pakistan who are exposed to saturated media consumption under the television. In addition to proudly contributing to the influence under the capturing idealism in the form of romantic, lovely, class-divided conflict created in society as well as the glorifying environment under the emotional intensity and dramatic relationship trajectories, the conceptualization of the Byronic heroes and sweeping heroine demonstrates the nomination to the specific trope under the shadow of the economic hypervreality. In order to ascertain the relationship between media consumption in terms of Pakistan specifically and the subsequent formation of unrealistic romantic beliefs, Gerbner's cultivation theory was examined under the quantitative survey and data was gathered from the questionnaire under the 160 female students from the various departments (N=160) of Sindh University Jamshoro. The five most popular dramas—Zindagi Gulzar Hai, Aik Thi Rania, College Gate, Mai Manto Nahi Hun, and Chemistry—enhanced the romantic expectation-based themes with their characters discussed in this study under the quantitative survey instruments and evaluated viewers on weekly and hourly binge-watching partners under the approach of idealism, unrealistic partial internalization, and unhappiness, which are the main components of the second. The cultivation theory presented in the data set analysis demonstrates the endorsement of romantic idealism expectations and shows a major significant relationship correlation in terms of dose response (=.42, p <.01) in terms of the viewers under the media consumption of more than five hours of the five dramas set in the week.In this sense, a main or core disparity in viewer expectations other than those of non-viewers was shown by the t-test applied to the independent sample (p <.001 for each). Furthermore, the study discovered an effect score with university students under the relationship study and the relationship status stated in the highest romantic anticipation under the romantic point of view. The media had a big impact on married and unmarried women; the results showed that 41% of them were under repression, and the younger and older women did not find a partner. Understand the important effects of Pakistani dramas and the romantic expectations of university students as a result of increased media consumption at the conclusion of the study's article.It causes media consumption to flourish. Its impact on digital platforms is more valued and fosters strong media connections under psychological well-being. Keywords: parasocial attraction, pakistan drams, romantic expectation, cultivation theory, idealism, psychological heath